2023
DOI: 10.3390/tropicalmed8040194
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the National Wetland Park in the Poyang Lake Area on Oncomelania hupensis, the Intermediate Host of Schistoma japonicum

Abstract: In this study, we aimed to understand the influence of ecotourism on the distribution of Oncomelania hupensis and to provide a scientific basis for formulating effective snail control methods in tourism development areas. Poyang Lake National Wetland Park was selected as the pilot area, and sampling surveys were conducted based on comprehensive and detailed investigations of all historical and suspected snail environments according to map data to determine the snail distribution and analyze the impact of touri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…These results indicated that there are still enough space to put the biological control strategy into practice in the marshlands of Poyang Lake. Here, no S. japonicum infections in snails were observed, indicating that the schistosomiasis control strategy has been effective in this area, but there is still a risk of schistosomiasis transmission ( Li et al, 2023 ). Therefore, it also reminds us to realize the necessity of applying for the alternative effective and environment-friendly schistosomiasis control strategies.…”
Section: Discussionmentioning
confidence: 92%
“…These results indicated that there are still enough space to put the biological control strategy into practice in the marshlands of Poyang Lake. Here, no S. japonicum infections in snails were observed, indicating that the schistosomiasis control strategy has been effective in this area, but there is still a risk of schistosomiasis transmission ( Li et al, 2023 ). Therefore, it also reminds us to realize the necessity of applying for the alternative effective and environment-friendly schistosomiasis control strategies.…”
Section: Discussionmentioning
confidence: 92%